Factors associated with fear and anxiety in patients attending a dental care: A cross-sectional study - Alzate Zapata, Luisa María; Garcia Bran , Saira Yurany; Gaviria Correa, Isabella; López Sarmiento, Jonathan Smith; Ortiz Restrepo, Juliana; Franco Aguirre, John Querubín; Gallego Gómez, Clara Liliana (Revista Estomatología, 2021)
Background: People who feel fear and anxiety show worse oral health conditions than those who not, thus delaying dentist appointments to the point of cancelling all together. Aim: Determine the degree of fear, anxiety and associated factors in patients seen in the clinics of the Faculty of Dentistry of the Universidad Cooperativa de Colombia. Materials and methods: A quantitative cross-sectional descriptive study was conducted with patients treated in clinics of the Faculty of Dentistry, for a universe of 941, a sample of 198 participants were calculated, not randomly selected. Three surveys were applied by the DFS (Dental Fear Survey), the MDAS (Anxiety Scale Modified Corah Dental) and a third survey to identify sociodemographic variables and factors associated with fear and anxiety. Results: The 92.4% of the participants presented some degree of fear in the dental practice. 48.7% have anxiety to some degree. The presence of fear and anxiety was found associated with the evaluation of previous experiences in dental practice (Vp <0.001), evidenced in the highest proportion of individuals with high fear and anxiety whose experience was negative compared to the frequencies observed for those with mild or moderate anxiety and zero or low fear. Conclusion: Previous traumatic experiences are related to fear and dental anxiety and can influence the proper development of the dental appointments, so it is recommended to inquire about these before starting with a dental treatment.